2016
DOI: 10.1111/1754-9485.12439
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG PETCT performed before and during radiation therapy of head and neck squamous cell carcinoma: Are they independent or complementary to each other?

Abstract: Addition of iPET significantly improves the prognostic values of all three metabolic parameters and can potentially be used in future adaptive local and systemic therapy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Only three of them measured it from the combination of tumor and lymph nodes volumes. [23][24][25] A fixed SUV was the main segmentation method used to obtain the VOIs threshold, 12,[22][23][24][25][26][27][28][29][30][31] followed by a percentage of SUVmax. 20,[32][33][34][35] One study used the mediastinal blood pool 36 and another one utilized an adaptive threshold.…”
Section: Studies Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three of them measured it from the combination of tumor and lymph nodes volumes. [23][24][25] A fixed SUV was the main segmentation method used to obtain the VOIs threshold, 12,[22][23][24][25][26][27][28][29][30][31] followed by a percentage of SUVmax. 20,[32][33][34][35] One study used the mediastinal blood pool 36 and another one utilized an adaptive threshold.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…21 MTV and TLG were measured alone as the main variable in seven 20,22,28,29,[31][32][33] and two 27,35 studies, respectively, and both variables were measured together in nine studies. 12,21,[23][24][25][26]30,34,36 Cut-off values were obtained through receiver operating characteristic curve (AUC-ROC), 12,21,[23][24][25][26]28,29,32,33,35,36 median values, 20,22,27 minimum P value, 34 difference between first and third tertile 31 and Q-statistic, 30 with an average of 15.38 mL for MTV and 96.21 g for TLG ( Table 3). The studies had a good quality according to NOS, as they all had a score higher than 6 ( Table 1).…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Seven studies (374 patients) evaluated the predictive value of PET performed during RT ± CT (Brun et al, 2002;Castaldi et al, 2012;Chen et al, 2014;Farrag et al, 2010;Hentschel et al, 2011;Min et al, 2016Min et al, , 2015. All but one of them found a correlation between PET parameters RT ± CT and clinical outcome.…”
Section: Predictive Value Of Quantitative Pet Parameters During Chemomentioning
confidence: 99%
“…All but one of them found a correlation between PET parameters RT ± CT and clinical outcome. In a study by Min et al, 100 patients received a PET before and 3 weeks after the beginning of treatment (Min et al, 2016). The authors showed that pre-treatment SUVMax and mid-treatment TLG were correlated with 2-year DFS in multivariate analysis (83% vs 71.4%, p = 0.0019 and 88.4% vs 77.2%, p = 0.012, respectively).…”
Section: Predictive Value Of Quantitative Pet Parameters During Chemomentioning
confidence: 99%
“…In contrast to dose-escalation approaches to R-ART, a separate treatment philosophy is to use interim diagnostic imaging to guide dose de-intensification in responders, with the goal to improve the acute and chronic toxicity profile of HNSCC RT. Preliminary work on correlating interim PET-CT tumor response to local-regional failure free survival (LRFS) has demonstrated that, in general, patients who have a more pronounced metabolic response by mid-treatment scan appear to have better long-term locoregional control [75][76][77]. These non-intervention studies have generated the exciting concept that interim PET-CT can select robust responders for dose de-intensification strategies, but no prospective data are yet available to prove the viability of this paradigm.…”
Section: Response-adapted Adaptive Radiotherapy (R-art)mentioning
confidence: 99%